Pharmacokinetic and safety profiles of mesalazine enema in healthy Chinese subjects: A single- and multiple-dose study - Cao, Yuran; Wang, Jingjing; Tang, Xingyu; Tian, Yan; Yu, Jicheng; Liang, Hong; Wu, Jufang; Chen, Yuancheng; Cao, Guoying; Zhang, Jing (PloS one, 2024)
Mesalazine is a well-established treatment for ulcerative colitis by oral or topical administration. However, the pharmacokinetic (PK) and safety profiles of mesalazine administered by an enema has not been clarified in Chinese population. We conducted an open-label study to assess the PK and safety profiles of mesalazine in 11 healthy Chinese subjects after receiving mesalazine enema (1 g/100 mL) once daily for 7 consecutive days. Blood and urine samples were collected for assay of mesalazine and N-acetyl mesalazine by liquid chromatography-tandem mass spectrometry. The PK and safety data were summarized using descriptive statistics. The mean (standard deviation) maximum plasma concentration (C max ), area under plasma drug concentration-time curve from time 0 to the last measurable plasma concentration time point (AUC 0- t) and elimination half-life (t 1/2 ) of mesalazine were 1007.64 (369.00) ng/mL, 9608.59 (3533.08) h·ng/mL and 3.33 (1.99) h, respectively after the first dose administration. In multiple-dose study, the estimated accumulation factor of mesalazine was 1.09. The cumulative urinary excretion rate of parent and major metabolite of mesalazine was 27.77%. After the last doe administration, 2.21% of the administered dose was excreted as mesalazine and 24.47% as N-acetyl mesalazine in urine within 24 h. Overall, 9 adverse events (AEs) were reported in 4 of the 11 subjects (36.4%), including oral ulcer, toothache, upper respiratory tract infection (1 each) and laboratory abnormalities (6 cases). All AEs were mild and recovered spontaneously without treatment, and were not considered as related to mesalazine. Mesalazine enema (1 g/100 mL) was safe and well tolerated in healthy Chinese subjects. These findings support further clinical trials in Chinese patients. Trial registration: This trial was registered to Chinese Clinical Trial Registry (ChiCTR) at https://www.chictr.org.cn (registration number: ChiCTR2300073148 ).